The effect of debt policy, company value, company size, investment cash flow on stock returns on mining companies listed on Indonesia Stock Exchange - Ardhia Prameswari Regita Cahyani; Carolyn Lukita Sembiring (STIE Perbanas Surabaya, 2019)
Investment is a delay in consumption now to be allocated to productive assets which are expected to generate profits in the future, which is called stocks return. Mining company in Indonesia is an attractive sector to invest in stocks because from a geographical perspective, Indonesia is an archipelago structure that contains mining products. There are risks that will be experienced by investors when investing, namely systematic risk and unsystematic risk. Unsystematic risk can be avoided because related to management decisions. Knowing and analyzing the effect of debt policy, firm value, company size, investment cash flow on stock returns on mining companies listed on the Indonesian Stock Exchange. The statistical method used in this study is multiple regression analysis. The sample in this study is a mining company that has go public and published audited financial statements 2013-2017 with 84 data processed consisting of 28 companies each year. The results of hypothesis testing can be concluded that debt policy and firm value have significant effect on stock returns while firm size and investment cash flow does not have significant effect on stock returns. Investor will be interested in investing in companies with good financial performance rather than bad financial performance.